Improving Students’ Critical Thinking by Employing Toulmin Pattern of Argumentation - Supriyadi, Agus (EDUCAFL: Journal on Education of English as Foreign Language, 2023)
Writing argumentative essays poses an enormous challenge for students. It requires them to have good critical thinking skills to provide facts and reasoning for their argumentative essay. Thus, this study aims to investigate the use of the Toulmin Model of Argument to improve students’ critical thinking as reflected in their argumentative essays. This study was conducted in SMA Negeri 2 Batu. The quasi-experiment research design was employed in which pre and post-tests were given to control and experiment groups to measure their critical thinking skills as well as their writing achievement. The populations are eleventh-grade students of SMA Negeri 2 Batu consisting of ten classes. The cooperative learning technique is used for teaching argumentative essays for both control and experiment groups. However, the Toulmin Pattern of Argumentations is introduced only for the experiment group. Data on students’ critical thinking skills and writing achievement are obtained from students’ essays. The findings show that the Toulmin Pattern of Argumentation can improve students’ critical thinking skills and writing achievement. It is proven by higher scores of critical thinking skills and writing achievement of the experiment group than those of the control group.